Agriculture drones: A modern breakthrough in precision agriculture. Issue 4 (4th July 2017) - Puri, Vikram; Nayyar, Anand; Raja, Linesh
Abstract: Drones commonly referred, as UAVs are mostly associated with military, industry and other specialized operations but with recent developments in area of sensors and Information Technology in last two decades the scope of drones has been widened to other areas like Agriculture. The drones manufactured these days are becoming smarter by integrating open source technology, smart sensors, better integration, more flight time, tracking down criminals, detecting forest and other disaster areas. The aim of this research paper is to highlight the importance of drones in agriculture and elaborate top drones available in market for Agriculture monitoring and observation for yielding better crop quality and preventing fields from any sort of damage.